Genome-wide association study identified genes associated with ammonia nitrogen tolerance in Litopenaeus vannamei - Fu, Shuo; Liu, Jianyong (Frontiers in Genetics, 2022)
Ammonia nitrogen tolerance is an economically important trait of the farmed penaeid shrimp Litopenaeus vannamei. To identify the genes associated with ammonia nitrogen tolerance, we performed an extreme phenotype genome-wide association study method (XP-GWAS) on a population of 200 individuals. The single nucleotide polymorphism (SNP) genotyping array method was used to construct the libraries and 36,048 SNPs were found in the genome of L. vannamei. Six different SNPs, located on SEQ3, SEQ4, SEQ5, SEQ7, and SEQ8, were determined to be significantly associated with ammonia nitrogen tolerance. By integrating the results of the GWAS and the biological functions of the genes, seven candidate genes (PDI, OZF, UPF2, VPS16, TMEM19, MYCBP2, and HOX7) were found to be associated with ammonia nitrogen tolerance in L. vannamei. These genes are involved in cell transcription, cell division, metabolism, and immunity, providing the basis for further study of the genetic mechanisms of ammonia nitrogen tolerance in L. vannamei. Further candidate gene association analysis in the offspring population revealed that the SNPs in the genes zinc finger protein OZF-like (OZF) and homeobox protein Hox-B7-like (HOX7) were significantly associated with the ammonia nitrogen tolerance trait of L. vannamei. The identified SNPs will also provide useful information for marker-assisted selection in L. vannamei.